2012
DOI: 10.1063/1.4712425
|View full text |Cite
|
Sign up to set email alerts
|

High-output-power densities from molecular beam epitaxy grown n- and p-type PbTeSe-based thermoelectrics via improved contact metallization

Abstract: Electrical power densities of up to 33 W/cm2 and up to 12 W/cm2 were obtained for n-type and p-type PbTeSe-based stand-alone thermoelectric devices, respectively, at modest temperature gradients of ∼200 °C (Tcold = 25 °C). These large power densities were enabled by greatly improving electrical contact resistivities in the thermoelectric devices. Electrical contacts with contact resistivities as low as 3.9 × 10−6 Ω cm2 and 4.0 × 10−6 Ω cm2 for n- and p-type telluride-based- materials, respectively, were develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…6 Using a complex in-vacuo process, Goodhue et al have shown that atomic hydrogen cleaning followed by in situ metalized titanium/nickel/gold contacts can yield oxide-and carbon-free interfaces, but the large ultimate R c $ 4 Â 10 À6 X cm 2 suggests the benefits to R c from surface cleaning alone are somewhat limited. 7 To obtain clean surfaces for the present (Bi,Sb) 2 (Se,Te) 3 samples, we employ a simple HCl clean immediately before metallization, following the work of Fang. 8 In this work, an alternate approach to reduce R c is described that simultaneously reduces the R c and eliminates the problem of chemical interdiffusion at the contact.…”
mentioning
confidence: 99%
“…6 Using a complex in-vacuo process, Goodhue et al have shown that atomic hydrogen cleaning followed by in situ metalized titanium/nickel/gold contacts can yield oxide-and carbon-free interfaces, but the large ultimate R c $ 4 Â 10 À6 X cm 2 suggests the benefits to R c from surface cleaning alone are somewhat limited. 7 To obtain clean surfaces for the present (Bi,Sb) 2 (Se,Te) 3 samples, we employ a simple HCl clean immediately before metallization, following the work of Fang. 8 In this work, an alternate approach to reduce R c is described that simultaneously reduces the R c and eliminates the problem of chemical interdiffusion at the contact.…”
mentioning
confidence: 99%
“…MBE is a novel method for the epitaxial preparation of thin film materials and has also been used in recent years for the preparation of skutterudite TE thin film materials [67][68][69][70][71]. MBE is a novel process for coating on substrates under ultra-high vacuum.…”
Section: Molecular Beam Epitaxy (Mbe)mentioning
confidence: 99%